The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/w11112352
|View full text |Cite
|
Sign up to set email alerts
|

Streamflow and Sediment Declines in a Loess Hill and Gully Landform Basin Due to Climate Variability and Anthropogenic Activities

Abstract: Streamflow and sediment runoff are important indicators for the changes in hydrological processes. In the context of environmental changes, decreases in both streamflow and sediment (especially in the flood season) are often observed in most of the tributaries of the middle Yellow River in China’s Loess Plateau. Understanding the effect of human activities could be useful for the management of soil and water conservation (SWC) and new constructions. In this paper, changes in streamflow and sediment during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…However, numerous contributions have pointed out the sediment load reduction experienced by many rivers as a result of human activities (Chang et al, 2019;Dang et al, 2010;Dearing & Jones, 2003;Golosov & Walling, 2019;Gupta et al, 2012;Hu et al, 2009;Hu et al, 2019;Latrubesse et al, 2017;Li et al, 2016;Miao et al, 2011;Rahman et al, 2018;Shi et al, 2017;Vinh et al, 2014;Wang et al, 2011;Wang et al, 2015;Wu et al, 2018;Yang et al, 2002;Yang et al, 2015;Yu et al, 2013;Zhang et al, 2016;Zhou et al, 2016). Reservoir construction, and other modifications of river courses, considerably reduces connectivity between erosion areas in the basins and channel sectors downstream dams, the latter playing a main role (Kondolf, 1997;Graf, 1999Graf, , 2001Graf, , 2005Graf, , 2006Magilligan & Nislow, 2001, 2005Magilligan et al, 2003;Nilsson et al, 2005;Petts, 2009;Dai & Liu, 2013;Magilligan et al, 2013;Petts & Gurnell, 2013;Pal, 2016).…”
Section: 1029/2019ef001305mentioning
confidence: 99%
See 1 more Smart Citation
“…However, numerous contributions have pointed out the sediment load reduction experienced by many rivers as a result of human activities (Chang et al, 2019;Dang et al, 2010;Dearing & Jones, 2003;Golosov & Walling, 2019;Gupta et al, 2012;Hu et al, 2009;Hu et al, 2019;Latrubesse et al, 2017;Li et al, 2016;Miao et al, 2011;Rahman et al, 2018;Shi et al, 2017;Vinh et al, 2014;Wang et al, 2011;Wang et al, 2015;Wu et al, 2018;Yang et al, 2002;Yang et al, 2015;Yu et al, 2013;Zhang et al, 2016;Zhou et al, 2016). Reservoir construction, and other modifications of river courses, considerably reduces connectivity between erosion areas in the basins and channel sectors downstream dams, the latter playing a main role (Kondolf, 1997;Graf, 1999Graf, , 2001Graf, , 2005Graf, , 2006Magilligan & Nislow, 2001, 2005Magilligan et al, 2003;Nilsson et al, 2005;Petts, 2009;Dai & Liu, 2013;Magilligan et al, 2013;Petts & Gurnell, 2013;Pal, 2016).…”
Section: 1029/2019ef001305mentioning
confidence: 99%
“…Walling and Fang (2003), studying sediment load in 145 large river basins for a period >25 years, found that about 70 showed no significant change, 68 showed reductions attributable to reservoir construction, and 7 experienced increases that could be explained by land use changes. Many other contributions (Wang et al, 2007(Wang et al, , 2011Zhang & Lu, 2009;Miao et al, 2011;Du & Shi, 2012;Gupta et al, 2012;Yang et al, 2015;Li et al, 2016;Liu et al, 2017;Wu et al, 2018;Hu et al, 2019;Chang et al, 2019) have attributed the reduction of sediment load mainly to human activities, among which dams appear to be the most important. In particular, Yang et al (2015) concluded that between 1950-1968 and 2003-2012 the reduction of sediment load observed in rivers could be explained by reservoirs (~88%), other human activities (~7%), and rainfall changes (~5%); and Syvitski et al 200510.1029/2019EF001305…”
Section: 1029/2019ef001305mentioning
confidence: 99%
“…Since the 1950s, some engineering and biological measures such as fish‐scale pits, level ditches, level benches, terraces, and afforestation have been implemented on the Loess Plateau of China (Chen et al, 2020; Zhao et al, 2017). Soil and water loss was further reduced with the implementation of the “Grain for Green” project from 1999 (Chang et al, 2019; Fu et al, 2017). The average annual sediment flux from 2000 to 2010 (0.32 ± 0.24 Gt year −1 ) across the Loess Plateau was less than one quarter of that from 1950 to 1980 (1.34 ± 0.24 Gt year −1 ) (Wang, Fu, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Climate change and anthropogenic activities pose a substantial risk of river system alterations [1][2][3]. The changes in environmental processes have important implications on hydrologic and sediment cycles.…”
Section: Introductionmentioning
confidence: 99%